POTENSI EKSTRAK ETANOL KULIT BUAH MATOA (Pometia pinnata J.R Forst & G.Forst) TERHADAP BAKTERI PENYEBAB KARIES GIGI - Mahdalena Sy Pakaya; Jihan Astuti Kai; Wiwit Zuriati Uno (Jambura Journal of Chemistry, 2021)
One of the infectious diseases that occur in the oral cavity is dental caries (cavities). The bacteria that play a role in the occurrence of infection are Streptococcus mutans bacteria, and the matoa plant is one of the plants that can act as antibacterial (Pometia pinnata J.R Forst) which has high efficacious compounds. This study aimed to determine the activity and potency of the ethanolic extract of matoa fruit peel (Pometia pinnata J.R Forst & G. Forst) against Streptococcus mutans bacteria. This research is a laboratory experimental research. Matoa fruit peel simplicia was extracted by maceration method with 96% ethanol solvent, then tested for phytochemical screening to determine the class of compounds contained in the matoa fruit peel. Furthermore, the activity was tested against Streptococcus mutans bacteria using a positive control of chloramphenicol antibiotics and a negative control of Dimethyl Sulfoxide. After that, the values of the Minimum Inhibitory Level and Minimum Killer were measured. From these results, it was continued to test the antibacterial potential using the Kirby Bauer method. The results showed that the ethanol extract of matoa fruit peel (Pometia pinnata J.R Forst & G. Forst) had activity against Streptococcus mutans bacteria. The potential value of the matoa fruit peel extract against Streptococcus mutans bacteria at concentrations of 25%, 50% and 75%, respectively, was 11.75 mm, 15.82 mm and 18.75 mm which was included in the category of strong inhibition.